Brain Aging and Electrophysiological Signaling: Revisiting the Spreading Depression Model - Guedes, Rubem Carlos Araújo; Abadie-Guedes, Ricardo (Frontiers in Aging Neuroscience, 2019)
As a consequence of worldwide improvement in health care, the aging portion of the human population has increased, now representing a higher proportion of the total population. This fact raises great concern regarding how to age while maintaining good brain function. Very often, alterations in brain electrophysiological signaling are associated with age-dependent functional disorders of the brain. Therefore, animal models suitable for the study of age-related changes in electrical activity of the brain can be very useful. Herein, we review changes in brain electrophysiological features as a function of age by analyzing studies in the rat brain on the phenomenon known as cortical spreading depression (CSD). Alterations in the brain’s capability to generate and propagate CSD may be related to differences in the propensity to develop certain neurological diseases, such as epilepsy, stroke, and migraine, which can biunivocally interact with the aging process. In this review, we revisit ours and others’ previous studies on electrophysiological features of the CSD phenomenon, such as its velocity of propagation and amplitude and duration of its slow negative DC shift, as a function of the animal age, as well as the interaction between age and other factors, such as ethanol consumption, physical exercise, and nutritional status. In addition, we discuss one relatively new feature through which CSD modulates brain signaling: the ability to potentiate the brain’s spontaneous electrical activity. We conclude that the CSD model might importantly contribute to a better understanding of the aging/brain signaling relationship.